1970
DOI: 10.3126/jnhrc.v7i1.2273
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Liver Diseases

Abstract: Background: The knowledge of distribution and pattern of liver disease in a tertiary care center provides an overview of disease pattern in a community. It also helps in planning and prioritizing strategies to treat the diseases and reduce their burden in the community. Methods: A retrospective study was conducted among patients admitted to the Liver unit, Bir Hospital from April 13, 2008 to October 16, 2008. Demographic profile and disease pattern was studied. Descriptive analysis was used to calculate frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
0

Year Published

1970
1970
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 7 publications
7
24
0
Order By: Relevance
“…9 In a retrospective study involving all consecutive patients admitted to the liver unit of Bir hospital from April 13, 2008 to October 16, 2008, it was found that, the most important predisposing factor for Liver abscess is the consumption of alcohol. 10 In our study also 95% of patients with liver abscess are giving a history of consuming alcohol. Among them 86% are giving the history of consuming locally prepared alcohol, which is found to be correlating with the above studies.…”
Section: Discussionsupporting
confidence: 51%
“…9 In a retrospective study involving all consecutive patients admitted to the liver unit of Bir hospital from April 13, 2008 to October 16, 2008, it was found that, the most important predisposing factor for Liver abscess is the consumption of alcohol. 10 In our study also 95% of patients with liver abscess are giving a history of consuming alcohol. Among them 86% are giving the history of consuming locally prepared alcohol, which is found to be correlating with the above studies.…”
Section: Discussionsupporting
confidence: 51%
“…16 Other group of investigators in Nepal, reported alcohol accounting for 60.8% of CLD. 17 Of several complications of chronic liver disease, hepatic Encephalopathy is an important one. 14.9% of patients with CLD are reported to have HE in previous study in Nepalese population.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study done in 2008 in Liver unit of Bir hospital showed that chronic alcohol consumption related Liver Disease account for 38.5% of inpatients followed by viral hepatitis 33.8%. 5 The grade of EVs often correlates with the severity of liver disease. While approximately 85% of individuals with Child-Turcotte Pugh (CTP) C cirrhosis have varices, they are present in only 45% in CTP A cirrhosis.…”
Section: Introductionmentioning
confidence: 99%